2022
DOI: 10.25259/jcis_126_2022
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on microwave ablation of liver lesions in difficult locations

Abstract: Microwave ablation (MWA) is becoming the standard of care in treating liver lesions smaller than 3 cm benefiting from a plethora of radiofrequency ablation (RFA) data in the literature. Some of the advantages of MWA compared to RFA are as follows: Faster ablations, more reproducible and predictable heating, better thermal conductivity in different liver tissue environments, and less susceptibility to heat-sink effect. Despite its many advantages, there are still concerns regarding MWA use in high-risk location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…10 Historically, certain high-risk locations, such as adjacent to the portal veins, bile ducts, and heart, were considered prohibitive for thermal ablation; however, recent studies showed encouraging results that MWA in such areas is relatively safe and effective when precaution is used. 5,11,12 While the literature provides evidence supporting the safety of utilizing MWA in challenging locations like proximity to the heart, near the diaphragm, and adjacent to the hepatic hilum, additional precautionary measures can be performed based on the skill and experience of the proceduralist to enhance safety. 5,11,12 Numerous retrospective evaluations have indicated that the combination of transarterial chemoembolization (TACE) and ablation could potentially yield oncological outcomes comparable to surgical resection, particularly for lesions smaller than 3 cm.…”
Section: Thermal Ablation For Small Hccmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Historically, certain high-risk locations, such as adjacent to the portal veins, bile ducts, and heart, were considered prohibitive for thermal ablation; however, recent studies showed encouraging results that MWA in such areas is relatively safe and effective when precaution is used. 5,11,12 While the literature provides evidence supporting the safety of utilizing MWA in challenging locations like proximity to the heart, near the diaphragm, and adjacent to the hepatic hilum, additional precautionary measures can be performed based on the skill and experience of the proceduralist to enhance safety. 5,11,12 Numerous retrospective evaluations have indicated that the combination of transarterial chemoembolization (TACE) and ablation could potentially yield oncological outcomes comparable to surgical resection, particularly for lesions smaller than 3 cm.…”
Section: Thermal Ablation For Small Hccmentioning
confidence: 99%
“…5,11,12 While the literature provides evidence supporting the safety of utilizing MWA in challenging locations like proximity to the heart, near the diaphragm, and adjacent to the hepatic hilum, additional precautionary measures can be performed based on the skill and experience of the proceduralist to enhance safety. 5,11,12 Numerous retrospective evaluations have indicated that the combination of transarterial chemoembolization (TACE) and ablation could potentially yield oncological outcomes comparable to surgical resection, particularly for lesions smaller than 3 cm. One meta-analysis found that combination of interventional therapies such as TACE and RFA seem to be more effective than RFA alone.…”
Section: Thermal Ablation For Small Hccmentioning
confidence: 99%
See 2 more Smart Citations
“…Liver tumors are predominantly treated using heat-based ablation, and in the United States MWA has largely replaced RFA, with cold-based techniques via cryoablation used much less commonly. 1,2 Early cryoablation techniques in the liver used an open surgical method in conjunction with large probes and nitrogen cryogen. [3][4][5] A retrospective analysis of these early procedures in liver tumors raised concerns about cryoshock and hemorrhage that influenced the subsequent era of thermal ablation procedures, and cryoablation was relegated as a riskier alternative to RFA.…”
mentioning
confidence: 99%